Molecular profiling of postreperfusion milieu determines acute kidney injury after liver transplantation: A prospective study. Issue 7 (23rd July 2018) - Pulitano, Carlo; Ho, Phong; Verran, Deborah; Sandroussi, Charbel; Joseph, David; Bowen, David G.; McCaughan, Geoffrey W.; Crawford, Michael; Shackel, Nicholas
Abstract : Acute kidney injury (AKI) after liver transplantation (LT) is a common event, but its pathogenesis remains unclear. The aim of this prospective study is to investigate the potential relationship between postreperfusion gene expression, serum mediators, and the onset of AKI after LT. Sixty‐five consecutive patients undergoing LT were included in the study. Reverse transcription polymerase chain reaction (PCR) was performed on liver biopsies. Gene expression of 23 genes involved in ischemia/reperfusion injury (IRI) was evaluated. The serum concentrations of endothelin (ET)–1 and inflammatory cytokines were analyzed. AKI after LT developed in 21 (32%) recipients (AKI group). Reverse transcription PCR of reperfusion biopsy in the AKI group showed higher expression of several genes involved in IRI compared with the non‐AKI group. Fold changes in the gene expression of ET‐1, interleukin (IL) 18, and tumor necrosis factor α (TNF‐α) were associated with creatinine peak value. AKI patients also had significantly higher ET‐1, IL18, and TNF‐α postoperative serum levels. Multivariate analysis showed that ET‐1 (odds ratio [OR], 16.7; 95% confidence interval [CI], 3.34‐83.42; P = 0.001) and IL18 (OR, 5.27; 95% CI, 0.99‐27.82, P = 0.048) serum levels on postoperative day 1 were independently predictive of AKI. Receiver operating characteristic analysis demonstrated that the combination of biomarkers ET‐1+IL18 was highly predictive of AKI (area under the receiver operating characteristic curve, 0.91; 95% CI, 0.83‐0.99). Early allograft dysfunction and chronic kidney disease stage ≥ 2 occurred more frequently in AKI patients. These results suggest that the graft itself, rather than intraoperative hemodynamic instability, plays a main role in AKI after LT. These data may have mechanistic and diagnostic implications for AKI after LT. Liver Transplantation 24 922–931 2018 AASLD.